Approximate Calculation of Nonstationary Temperature Regime of a Rock-Ice Dam (O Priblizhennom Raschete Nestatsionarnogo Temperaturnogo Rezhima Kamennoledianoi Plotiny) - Ukhova,N V (1977)
This article is devoted to studies concerning development of principles for calculating nonstationary temperature regimes of rock-ice dams. (Author) Trans. of Trudy Koordinatsionnykh Soveshchanii po Gidrotekhnike (USSR) v23 p160-172 1965.